Most recent and emerging technologies forenhancing the nutritional characteristics of food, challenges and future directions: A Review - Ore Areche, Franklin (2024)
The rapid advancement of emerging technologies is transforming the food industry, especially in enhancing the nutritional qualities of food. These innovations have significant potential for tackling global nutritional deficiencies and promoting public health. Key technologies include precision fermentation, which enables the production of high-quality proteins and micronutrients while minimizing environmental impact. Additionally, gene editing techniques such as CRISPR allow for the development of crops with improved nutrient profiles and enhanced resistance to pests and diseases. Furthermore, advancements in nanotechnology enhance the fortification of foods with essential vitamins and minerals, improving their bioavailability and stability. Personalized nutrition, driven by big data and artificial intelligence, customizes dietary recommendations based onindividual geneticprofiles, optimizing nutrient intake and health outcomes. This review article overviews these cutting-edge technologies and their applications in creating a more nutritious and sustainable food system.